Abrus agglutinin promotes irreparable DNA damage by triggering ROS generation followed by ATM‐p73 mediated apoptosis in oral squamous cell carcinoma. Issue 11 (21st August 2017) - Sinha, Niharika; Panda, Prashanta K.; Naik, Prajna P.; Das, Durgesh N.; Mukhopadhyay, Subhadip; Maiti, Tapas K.; Shanmugam, Muthu K.; Chinnathambi, Arunachalam; Zayed, ME; Alharbi, Sulaiman A.; Sethi, Gautam; Agarwal, Rajesh; et al.
Abstract : Oral cancer, a type of head and neck cancer, is ranked as one of the top most malignancies in India. Herein, we evaluated the anticancer efficacy of Abrus agglutinin (AGG), a plant lectin, in oral squamous cell carcinoma. AGG selectively inhibited cell growth, and caused cell cycle arrest and mitochondrial apoptosis through a reactive oxygen species (ROS)‐mediated ATM‐p73 dependent pathway in FaDu cells. AGG‐induced ROS accumulation was identified as the major mechanism regulating apoptosis, DNA damage and DNA‐damage response, which were significantly reversed by ROS scavenger N‐acetylcysteine (NAC). Moreover, AGG was found to interact with mitochondrial manganese‐dependent superoxide dismutase that might inhibit its activity and increase ROS in FaDu cells. In oral cancer p53 is mutated, thus we focused on p73; AGG resulted in p73 upregulation and knock down of p73 caused a decrease in AGG‐induced apoptosis. Interestingly, AGG‐dependent p73 expression was found to be regulated by ROS, which was reversed by NAC treatment. A reduction in the level of p73 in AGG‐treated shATM cells was found to be associated with a decreased apoptosis. Moreover, administration of AGG (50 μg/kg body weight) significantly inhibited the growth of FaDu xenografts in athymic nude mice. In immunohistochemical analysis, the xenografts from AGG‐treated mice displayed a decrease in PCNA expression and an increase in caspase‐3 activation as compared to the controls. In conclusion, we established a connection among ROS, ATM and p73 in AGG‐induced apoptosis, which might be useful in enhancing the therapeutic targeting of p53 deficient oral squamous cell carcinoma.